IMAGE OF HUMAN IN THE POSTMODERN EPOCH - L. M. Mykulanynets (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Based on the study of philosophical anthropological concepts, to highlight the project of personality in different historical periods, to reveal the meaning of humanistic issues in the postmodern epoch, to identify the essential features of the image of human of the second half of the XX the beginning of the XXI century. Theoretical basis. The methodological basis of the article is the principles of historicism, integrity, objectivity regarding the mastery of the issue of person’s image in postmodernism. The research applied comparative-historical, culturological, analytical, axiological approaches to reveal the problem of individuality in the second half of the XX the beginning of the XXI century. The theoretical basis of the article consists of scientific works in the field of philosophical anthropology, history, cultural studies, and aesthetics. Originality. The author revealed the peculiarities of transformation of the personality model from antiquity to postmodernism, specified the image of man of the second half of the XX the beginning of the XXI century. Conclusions. The analysis of anthropological ideas of Western philosophy of different ages shows the variety of views about understanding the nature of the person, its complexity and ambiguity. In the epoch of postmodernism humanistic issues are of particular relevance, which is connected with social and political uncertainty, domination of mass consciousness, loss of national and cultural identity. The image of a person of this period is deprived of a solid foundation, it is blurred and relative. The destruction of faith in the absolute in the context of the second half of the twentieth century contributed to the formation of confidence in the interdependence of all things (including certain historical periods), raised the problem of the personality image to a new ontological level. Orientation in the achievements of European civilization, perception of its anthropological experience, intercultural dialogue contribute to the productive use of the achievements of mankind in order to understand the modern person and to form its adequate image. In its essence, postmodernism does not set the goal to realize a retrospection of subject type. However, separating from the cultural memory the excerpts of ideas about a person, by certain styles and directions, it builds on their formations its own eclectic image of the individual.